Economic and Legal Dimensions of Collateral Existence in Modern Mudhârabah Contracts: Understanding the Relationship between Risk Management, National Law, and Contemporary Fiqh - Muhammad Syarif Hidayatullah; Rahmat Fadillah (Al-Manahij: Jurnal Kajian Hukum Islam, 2022)
This paper examines the economic and legal dimensions of the existence and application of collateral in modern mudhârabah contracts. Through this multi-perspective study, this paper sought to see the relationship between risk management, national law, and contemporary fiqh in discussing the existence and application of the collateral. This paper was included in the library research design and specifically in legal research methodology, applying normative legal research types with a conceptual and statutory approach. Furthermore, this research found a relationship between risk management, national law, and contemporary fiqh in viewing the existence of collateral applied to modern mudhârabah contracts in Sharia banking through its financing products. Based on the perspective of risk management, its existence was a risk control for non-performing financing. Then, in the perspective of national law, it manifested the prudential principle mandated by the sharia banking law. Meanwhile, in the perspective of contemporary fiqh, it can be seen as an effort to avoid the harm that was in line with the sadd adz-dzari'ah principle. This relationship was realized by looking at the existence of collateral in modern mudhârabah contracts as a preventive instrument.